Der Neü Layenspiegel von Ulrich Tengler Das deutschsprachige Augsburger Rechtsbuch zwischen Mittelalter und Neuzeit Europas - Möllers, Thomas M. J.; Becker, Christoph; Wolf, Klaus (Mohr Siebeck, 2025)
The Laienspiegel was one of the first comprehensive law books to be written in German. For over a century, it influenced the development of law in the German-speaking world. What were the consequences of this for legal practice at the time? The present volume takes an interdisciplinary look at this question from the perspective of legal history, Germanic studies and the history of art.
PublicationDate: 20250416
Keywords: Reformation -- Humanismus -- Rechtsbuch der frühen Neuzeit -- Juristisches Lehrbuch für Laien -- Illustrationen -- Geografie im 18. Jahrhundert -- empirische Ästhetik -- book of nature -- ritual bath -- ritual impurity -- Rechtsgeschichte -- Römisches Recht